Clinicopathological study of patients with head and neck sarcomas - Pacheco,Isabela Alves (2011)
Sarcomas are rare tumors, mainly stemming from the embryonic mesoderm, with a high grade of morbidity and mortality. OBJECTIVE: To carry out a retrospective study of head and neck sarcoma cases between 1999 and 2008 in three specialized centers in the city of Fortaleza. MATERIALS AND METHODS: Data collection was based on the charts of the patients in the study. For statistical analysis purposes we used the chi-square associations and the z test for proportions. RESULTS: We found records of 36 patients, and the most affected ones were adult brown males, in the age range between 20 and 59 years - mean age of 39.7. The man/woman ratio was 1.76:1. The most prevalent histological type was the rhabdomyosarcoma and their most common locations were the face and the neck. Most of the sample was made up of live patients without evidence of the disease in the last visit - 41.6% of the cases. The most common treatment modes were the combination of surgery + radiotherapy + chemotherapy and surgery + radiotherapy, with 27.8% of the cases each. CONCLUSION: Sarcomas have a great histological variability and may have numerous locations. Since these are rare and not well-known lesions, new epidemiological studies must be carried out in order to enhance our understanding of the disease.